Understanding interfacial dispersions in ecobenign polymer nano-biocomposites - Idumah, Christopher Igwe; Obele, Chizoba May; Ezeani, Emmanuel Obumneme (Polymer-plastics technology and engineering, 2021)
The advent of nanotechnology, and hybridization of nanomaterials such as graphene, carbon nanotubes, nanoclay and so on, with natural fibers in polymeric materials have resulted in formation of polymer fiber nano-biocomposites. Accruable properties garnered from these materials amongst many include thermal stability, enhanced electrical and thermal conductivity, reduced thermal expansion, enhanced heat deflection temperature, and improved ﬂame retardancy. This has enlarged the scope of application of these materials in the up-and-downstream industries. Therefore, this paper elucidates emerging nanotechnological advancement, interfacial interactions, and nanoparticles dispersion in plant fiber polymer nano-biocomposites.